1989
DOI: 10.1111/j.1442-9993.1989.tb01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of eucalypt species to drought

Abstract: The response of three eucalypt species (Eucalyptus pulchella. Eucalyptus coccifera and Eucalyptus delegatensisj to a severe drought in the summer of 1982/83 was examined at Snug Plains, south-eastern Tasmania. Few large differences in leaf water potential (\j/i) or stomatal conductance (gs) were apparent even at the height of the drought when both ii/i and soil water potentials (y/s) reachedca. -4.5 MPa. However. E. pulchella maintained a higher relative water content (RWC) in its leaves than E. coccifera and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…2). A similar lowering of leaf water potential reported for Eucalyptus wandoo (Colquhoun et al, 1984) and for Eucalyptus pulchella (Davidson and Reid, 1989) was associated with the ability to extract more water from the soil-a characteristic reported for eucalypts growing on drought prone sites (Doley, 1967;Ladiges, 1975;Clayton-Greene, 1983). The tendency to maintain relatively high gas exchange indicates little regulation of water loss as has been reported for E. marginata (Doley, 1967;Colquhoun et al, 1984), E. calophylla (Colquhoun et al, 1984), E. microcarpa (Attiwill and Clayton-Greene, 1984) and E. leucoxylon (Sinclair, 1980).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…2). A similar lowering of leaf water potential reported for Eucalyptus wandoo (Colquhoun et al, 1984) and for Eucalyptus pulchella (Davidson and Reid, 1989) was associated with the ability to extract more water from the soil-a characteristic reported for eucalypts growing on drought prone sites (Doley, 1967;Ladiges, 1975;Clayton-Greene, 1983). The tendency to maintain relatively high gas exchange indicates little regulation of water loss as has been reported for E. marginata (Doley, 1967;Colquhoun et al, 1984), E. calophylla (Colquhoun et al, 1984), E. microcarpa (Attiwill and Clayton-Greene, 1984) and E. leucoxylon (Sinclair, 1980).…”
Section: Discussionsupporting
confidence: 67%
“…Availability of water, nutrients and suitable temperatures are among the most important factors that limit plant productivity and yield across sites (Turner and Kramer, 1980;Kramer, 1983;Beadle and Turnbull, 1992;Landsberg, 1997). Studies of water relations of various eucalypts growing in their natural environments during times of severe drought have reported either avoidance or tolerance, or both mechanisms of adaptation, to water stress (Doley, 1967;Sinclair, 1980;Attiwill and Clayton-Greene, 1984;Davidson and Reid, 1989;Prior et al, 1997b;Prior and Eamus, 1999). Species that are profligate in their water use are reported to avoid tissue water deficit by maintaining access to a water source through deep root systems (Doley, 1967;Sinclair, 1980;White et al, 2000) enabling them to maintain high pre-dawn water potentials, relatively high stomatal conductance and presumably continued transpiration even under moderate water stress (Davidson and Reid, 1989;Abrams, 1990).…”
Section: Introductionmentioning
confidence: 96%
“…High relative water content of leaf is considered an adaptation to xeric conditions. Davidson & Reid (1989) studied the response of three Eucalyptus species to severe drought in the summer of 1982/83 at Snug Plains, south-eastern Tasmania, Australia and reported that E. pulchella maintained higher relative water content of leaf and is a relatively drought-resistant species. Pandey et al (1994) found that Prosopis chilensis contains high relative water content in leaf and grows successfully in dry regions of Western India.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, leaves with highly elastic tissues reduce steep declines in cell turgor because their cells contain more water at full turgor and can sustain larger declines in volume [1]. Pressure-volume relationships are routinely used to estimate these key parameters of leaf physiology [7] and are often interpreted as indicators of species drought tolerance i.e., the ability to maintain physiological function at low water status [8,9].…”
Section: Introductionmentioning
confidence: 99%